Correction: Kim et al. Spatial Distribution Pattern of the Mesozooplankton Community in Ross Sea Region Marine Protected Area (RSR MPA) during Summer. Diversity 2024, 16, 174 - Sung Hoon Kim; Wuju Son; Jeong-Hoon Kim; Hyoung Sul La (Diversity, 2024)
The authors realized that there were critical inaccuracies in their environmental data analysis, specifically related to chlorophyll (chl) and nutrient concentrations [...]